2015
DOI: 10.5539/ass.v11n4p157
|View full text |Cite
|
Sign up to set email alerts
|

E-lifestyle, Customer Satisfaction, and Loyalty among the Generation Y Mobile Users

Abstract: Technology advancement is gaining a great deal of attention among young individuals. Technology has significantly impacted and changed the context and the way young people live in recent years, particularly in developing countries across Southeast Asia. Indeed, telecommunication companies have noticed the importance of e-lifestyle factors which largely contribute to their identity. This research is aimed to examine the impact of e-lifestyle on customer satisfaction and loyalty from mobile consumers in the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Es estudio se realizó en noviembre y diciembre del 2022. El instrumento es una adaptación al propuesto por (Hassan et al, 2015) en E-lifestyle, customer satisfaction, and loyalty among the generation Y mobile users, consta de 28 ítems para medir cuatro Factores: Actividades Digitales (8 ítems; Intereses Digitales (7 ítems); Opinión sobre el Internet (6 ítems) y Valor del internet (7 ítems). El proceso adaptación y homologación del cuestionario consistió en obtener datos en relación a su fiabilidad (consistencia interna y test-retest), siendo los resultados para la prueba de alfa de Cronbach de (α=,883) y para el Coeficiente McDonald's de (ω=,880), siendo aceptables y evidenciando un nivel muy razonable de fiabilidad.…”
Section: Metodologíaunclassified
“…Es estudio se realizó en noviembre y diciembre del 2022. El instrumento es una adaptación al propuesto por (Hassan et al, 2015) en E-lifestyle, customer satisfaction, and loyalty among the generation Y mobile users, consta de 28 ítems para medir cuatro Factores: Actividades Digitales (8 ítems; Intereses Digitales (7 ítems); Opinión sobre el Internet (6 ítems) y Valor del internet (7 ítems). El proceso adaptación y homologación del cuestionario consistió en obtener datos en relación a su fiabilidad (consistencia interna y test-retest), siendo los resultados para la prueba de alfa de Cronbach de (α=,883) y para el Coeficiente McDonald's de (ω=,880), siendo aceptables y evidenciando un nivel muy razonable de fiabilidad.…”
Section: Metodologíaunclassified
“…Despite the numerous papers that have proved that there is a positive relationship between socialmediamarketingandbrandloyalty,thereareasufficientnumberofpapersthatpresentanew perspective. Laroche,Habibi,&Richard(2013) Demographic characteristics provide a relatively straightforward and reliable basis for segmentation (Blackwell et al, 2006;Koufaris, 2002), moreover, it has been shown to play a significantroleindeterminingthebehaviorofindividualsandwebusers (Girardetal.,2003).Based onthepreviousargument,inthecontextofourstudy,somedemographicvariables(gender,age, andeducation)willbeexaminedtodetermineiftheyaffecttherelationshipbetweensocialmedia marketingandbrandloyaltyamongsmartphoneusersinEgypt.Thesedemographiccharacteristics aremostpopularamongresearchers(e.g., Gironda,2014;Leung,2012;Kim&Ko,2012;Hassan, 2015)andtheyhaveadirectinfluenceonconsumers'lifestyleandbehaviorandrepresentindividual consumerdifferences (Dayanetal,2017).Therefore,thefollowinghypotheseshavebeenformulated:…”
Section: Social Media Marketing and Brand Loyaltymentioning
confidence: 99%
“…Adherence can be confirmed by evaluating the outer weight, which is the relative importance of each indicator, and the outer loading, which implies its absolute importance [51]. The outer weight is more than 0.1 [52], and the outer loading is more than 0.5 [53]. As a result of the analysis, it can be shown that all the criteria mentioned above are satisfied, so the application of the formative measurement model is appropriate.…”
Section: Evaluation Of Measurement Modelmentioning
confidence: 99%